INFORMATION SYSTEM DEVELOPMENT OF ELECTRIC CAR CHARGING STATIONS BY UNIFIED MODELLING LANGUAGE DIAGRAMS (REVUE ROUMAINE DES SCIENCES TECHNIQUES — SÉRIE ÉLECTROTECHNIQUE ET ÉNERGÉTIQUE, 2025)
This paper presents a high-level approach to developing an information system for electric car charging stations, utilizing a Process Layer Supply pattern. This pattern organizes activity processes, business rules, visions, and goals that support system modelling. The paper models the system's structural and behavioral aspects using UML diagrams—specifically, class, use case, and activity diagrams — via the Papyrus UML2 tool. These diagrams facilitate visualizing functional requirements, user-to-system interactions, and system components for efficient planning, development, and implementation. The model addresses the most critical gaps in an electric car charging infrastructure and optimizes the information system's operations for practical implementation. The proposed system is designed to support future developments, like integration with dynamic demand markets for flexible pricing and optimized operations. Additionally, we use pseudocode to link abstract UML models to actual implementations, ensuring the accurate transfer of system logic to the corresponding code. Since every component of the charging network is logically interconnected, a sustainable foundation for future electric car mobility is established.
Keywords: Information system; Electric car charging stations; Process layer supply; Unified modelling language (UML)